Analisis Pengaruh FDR dan BOPO terhadap Kinerja Keuangan (ROA dan ROE) pada Bank Syariah Indonesia - Fathmah Hanum; Mugiyati Mugiyati; Saiful Bakhri; Muhamad Ahsan (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
The establishment of Bank Syariah Indonesia (BSI) through the merger of three state-owned Islamic banks marked a significant transformation in Indonesia’s Islamic banking industry, creating new challenges and opportunities related to profitability, financing expansion, and operational efficiency. Financial performance during the post-merger period can be evaluated through profitability indicators, particularly Return on Assets (ROA) and Return on Equity (ROE), which reflect management effectiveness in utilizing assets and shareholders’ equity. Quarterly financial statement data from 2021–2025 were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression to examine the relationship between Financing to Deposit Ratio (FDR), Operational Efficiency Ratio (BOPO), and financial performance. The findings indicate that FDR is positively associated with profitability, suggesting that increased financing distribution contributes to improved financial returns. Conversely, BOPO demonstrates a strong negative relationship with both ROA and ROE, indicating that operational efficiency plays a decisive role in enhancing profitability. The regression results confirm that FDR and BOPO jointly explain a substantial proportion of variations in financial performance, with BOPO emerging as the more dominant determinant. These findings highlight that the success of BSI’s post-merger transformation is driven not only by financing growth but also by the ability to maintain operational efficiency. The study contributes empirical evidence on the financial dynamics of Indonesia’s largest Islamic bank during the post-pandemic recovery and institutional consolidation period.